'If you were an animal you would have eaten me': Animal's People and the history of corporate colonialism. Issue 1 (2nd January 2021) - Neti, Leila
ABSTRACT: Indra Sinha's novel Animal's People provides a fictional account of the 1984 Union Carbide toxic gas leak in Bhopal, India. Animal, who is severely injured in the disaster, guides the reader through both the post-apocalyptic social landscape, as well as the community's failed efforts to hold the 'Kampani' accountable for the consequences of the leak. Reading Animal's story through the lens of what I identify as its historical precedent, I trace the continuities between the Union Carbide Corporation and the East India Company in order to reveal in both moments a shared substitution of the corporation for the human. Bringing Animal's People into dialogue with this broader legal history, I argue that the terms of humanity set forth in the British colonial era rationalize the portrait of disposable humanity that Sinha paints. The guiding question of the paper is how does the legal realm shape and guide the imaginative possibilities of the human as represented in literature?